Building Student Discipline Through Classroom Management Strategies: A Qualitative Study in Indonesian Elementary Schools - Renita Renita; Yusdin Bin M Gagaramusu; Kadek Hariana; Rizal Rizal; Danti Indriastuti Purnamasari; Surahman Wilade (Papanda Publisher, 2026)
The decline in student discipline in elementary schools, exacerbated by globalization and technological advancement, necessitates effective classroom management strategies that foster intrinsic behavioral regulation rather than external compliance. This study examined classroom management strategies employed by fourth-grade teachers at SDN Bambalemo to cultivate student discipline and identified factors influencing their implementation. A qualitative descriptive design was employed, with data collected through systematic observations, in-depth interviews with four teachers (coded A1-A4), and documentation analysis. Data were analyzed using Miles and Huberman's interactive model, incorporating triangulation to ensure validity. Three primary strategies emerged: creating positive learning climates through warm teacher-student relationships and consistent modeling; organizing adaptive learning spaces that promote cooperation and ownership; and managing interactive teaching-learning processes through two-way communication and constructive feedback. Internal factors—including teacher personality, professional awareness, motivation, and growth mindset—and external factors—encompassing family support, school regulations, and community environments—significantly influenced strategy effectiveness. An unexpected finding revealed students spontaneously maintained classroom tidiness, indicating internalized responsibility. Student discipline develops through ecological processes involving habituation, role modeling, and multi-stakeholder collaboration rather than authoritarian control. The findings challenge punitive approaches while supporting relationship-based pedagogies that foster self-regulation, providing empirical foundations for character-based classroom management in elementary education.